Love and Knowledge: Emotion in Feminist Epistemology - Jaggar, Allison M. (Inquiry, 1989)
This paper argues that, by construing emotion as epistemologically subversive, the Western tradition has tended to obscure the vital role of emotion in the construction of knowledge. The paper begins with an account of emotion that stresses its active, voluntary, and socially constructed aspects, and indicates how emotion is involved in evaluation and observation. It then moves on to show how the myth of dispassionate investigation has functioned historically to undermine the epistemic authority of women as well as other social groups associated culturally with emotion. Finally, the paper sketches some ways in which the emotions of underclass groups, especially women, may contribute to the development of a critical social theory.
Keywords: discipline; genre; ressource en ligne; sciences humaines; théories féministes; émotions; épistémologie

Identité sexuelle/sexuée/de sexe? Trois modes de conceptualisation du rapport entre sexe et genre - Mathieu, Nicole-Claude (Catégorisation de sexe et constructions scientifiques, 1989)
Keywords: approches et analyses; corps; cours; discipline; discours dominant; essentialisation; féminisme matérialiste; genre; histoire et politique; identité sexuelle; identités; naturalisation; philosophie politique; premier cycle; sciences; sciences humaines; sex3383; sexe; sexe/genre; systèmes d'oppressions; thématiques; épistémologie; épistémologies féministes